EU General Data Protection Regulation (GDPR) - An Implementation and Compliance Guide (4th Edition) - IT Governance Publishing (IT Governance Publishing, 2020)
Now in its fourth edition, EU General Data Protection Regulation (GDPR) - An Implementation and Compliance Guide provides clear and comprehensive guidance on the GDPR. It explains the Regulation and sets out the obligations of data processors and controllers in terms you can understand. Topics covered include: The DPO (data protection officer) role, including whether you need one and what they should do; Risk management and DPIAs (data protection impact assessments), including how, when and why to conduct one; Data subjects' rights, including consent and the withdrawal of consent, DSARs (data subject access requests) and how to handle them, and data controllers and processors' obligations; Managing personal data internationally, including updated guidance following the Schrems II ruling; How to adjust your data protection processes to comply with the GDPR, and the best way of demonstrating that compliance; and A full index of the Regulation to help you find the articles and stipulations relevant to your organisation.